[LB.02.12] TLR4 ANTAGONISM PREVENTS EARLY LEFT VENTRICULAR HYPERTROPHY AND DYSFUNCTION ASSOCIATED WITH NEONATAL HYPEROXIA EXPOSURE. (September 2017) - Mian, M.; He, Y.; Bertagnolli, M.; Cloutier, A.; Luu, T.M.; Nuyt, A.M.
Abstract : Objective: Preterm birth is associated with proinflammatory/prooxidative status early in life, and increased risk of cardiovascular diseases (CVD) through mechanisms that are incompletely understood. Our lab has shown in rats that transient neonatal exposure to high O2, an established model of prematurity-related prooxidative conditions, leads to early CV inflammation and remodeling. TLR4 signaling is a critical link between inflammation and the pathogenesis of CVD. It is unknown whether neonatal programmed innate immunity activation, via TLR4 signaling, impacts long term CVD. In a rat model of prematurity (neonatal high O2 exposure), the current study investigated whether neonatal TLR4 antagonism will prevent the development of early CV dysfunction. Design and method: Male Sprague-Dawley pups were kept with their mother in 80% O2 or room-air from day (P) 3 to 10 of life. A subgroup was sacrificed at P10 to assess TLR4 protein expression. In other experiments, pups were treated i.p. with TLR4 antagonist LPSRS (100 μg/kg) or vehicle (0.9% NaCl) at P3, P6 and P9 (concomitant to O2 exposure; n = 6–9 per group, max 3 animals/group/liter). At 4 and 7 weeks, body weights were measured and left ventricular (LV) echocardiography was performed under isoflurane anesthesia using VEVO 3100 system (VisualSonics). Comparisons were made using Student's t-test or ANOVA. Results: At P10, cardiac TLR4 protein expression was increased ∼2 fold in hyperoxia-exposed pups compared to room-air controls (P < 0.05). At 4 weeks, body weight in vehicle- or LPSRS-treated hyperoxia animals (101 ± 2 g and 106 ± 2 g) was lower compared to room-air vehicles (117 ± 2 g, P < 0.01). Compared to room-air vehicles, vehicle-treated but not LPSRS-treated hyperoxia animals exhibited increased LV mass index (3.8 ± 0.1 and 3.4 ± 0.1 vs 3.3 ± 0.1 mg/g, P < 0.05 for hyperoxia vehicles vs room-air vehicles), reduced ejection fraction (74 ± 2 and 79 ± 2 vs 82 ± 1%, P < 0.05) and fractional shortening (43 ± 2 and 48 ± 2 vs 52 ± 2%, P < 0.01), reduced cardiac output index (0.43 ± 0.02 and 0.48 ± 0.02 vs 0.56 ± 0.03 ml/min/g, P < 0.01), and decreased mitral E-to-A wave ratio (1.3 ± 0.1 and 1.7 ± 0.1 vs 1.7 ± 0.1 mg/g, P < 0.01). Findings were similar at 7 weeks. Conclusions: TLR4 antagonism prevents early LV hypertrophy and mild systolic and diastolic dysfunction associated to neonatal exposure to hyperoxia.